Aged and quality of life: the social representation of elders living in the south of Minas Gerais state - Silva, José Vitor da; Kimura, Miako (Online Brazilian Journal of Nursing, 2004)
The aging of the population became a critical concern worldwide. There is no question that population aging is a concerning phenomenon. There are approximately 15 million elders among us.Yet, the elderly take a secondary place in the community as well as in the family. The sense of being useless and along appears as a consequence of family prejudice, dependence on progeny, being widow and being retired (Neri, 1993).The highest death rate is concentrated in elders aging 60 years and older, caused mainly by circulatory diseases, malign tumors and, metabolic and respiratory illness (Carvalho Filho, 1996).The chronic-degenerative diseases, typical of elders, as well as their complications and sequels are becoming progressively more relevant in our country. Longevity can be a problem of serious consequences to many dimensions of the human life, such as physical, psychological and social, showing important implications to the quality of life (Paschoal, 2002). Quality of Life - QL on elderly is a phenomenon that demands attention from demographers, social gerontologists and geriatricians. There is an increasing interest in the characterization of factors that determine the QL on elderly in terms of physical, psychological and social domains, as well as the identification of the current sense of such concept on the elderly people. At any moment of the life cycle in any society, QL is a multi face phenomenon, and therefore, it is better described by a multidimensional construction. This work aimed the identification of being elder and the QL, as seen by the elders. It is a qualitative study in which 50 elders, of both genders and living in Itajubá, Pouso Alegre and Santa Rita do Sapucaí were interviewed. The interview followed a pre set format. It was recorded and entirely transcripted. In order to know and to describe the meaning of QL for the elders, it was used the theoretic referential methodology of the Social Representation Theory in which the knowledge is analyzed by using stories at individual and social levels of the interviewee (Jodelet, 1985) as in the Collective Subject Speech - CSS. The Collective Subject Speech method consists of joining in a single speech – the synthesis, many individual speeches issued as answers to the same question of the interview, by social and institutional equivalence or that are part of the same organizational culture, and from a homogeneous social group, as the individuals of the group occupy the same, or close, social positions (Lefèvre, 2002). The CSS methodological directions were used to select the main ideas and the expressions – corresponding keys, were the elder speeches were obtained. Some social representations about “being elder” were identified: incapable or functionally unable person; very old but full of healthy and willing to work; full of life experience, already lived and fulfilled the life expectations. The social representations about the concept of QL were established on many dimensions: physical health; physical independence; psychological, social and financial autonomy; family; religion and transcendence; environment and citizenship. This work confirmed the multidimensional and multidetermined view of the phenomena studied, related to many objective and subjective aspects of the human life.